Dampak Model Problem Based Learning Terhadap Keterampilan Abad 21 (4 C) di Sekolah Dasar - Endang Indarini (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
Educators in carrying out learning planning assignments should consider students' needs. Learning strategy is needed for learners for 21st century life skills in learning planning in order to obtain the meaning of learning. This study is to determine the impact of the Problem Based Learning model on 21st century skills (4C) in elementary schools from experimental research published by the meta-analysis method. The research sample of the search results was 40 articles with an average pretest of 54.13 and posttest of 74.33 there was an increase of 20.20. The results of the Effect Size test using the Problem Based Learning model on 21st century skills (4C) have a result of 0.717 with a Sig. value of 0.000. These results obtained show that the effect of the Problem Based Learning model on 21st century skills (4C) in elementary schools has a relatively large impact. The relatively large influence can be used as a recommendation for teachers to plan learning with the Problem Based Learning model in training students' cognitive processes through the application of 4C skills.